2015
DOI: 10.1111/papq.12129
|View full text |Cite
|
Sign up to set email alerts
|

Justified Belief from Unjustified Belief

Abstract: Under what conditions is a belief inferentially justified? A partial answer is found in Justification from Justification (JFJ): a belief is inferentially justified only if all of the beliefs from which it is essentially inferred are justified. After reviewing some important features of JFJ, I offer a counterexample to it. Then I outline a positive suggestion for how to think about inferentially justified beliefs while still retaining a basing condition. I end by concluding that epistemologists need a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…It is a case of justified true belief from unjustified true belief as opposed to knowledge from falsehood. That said, the seat counter case does bear some resemblance to a case discussed by Murphy (). In Murphy's case, someone called Fred has a memory based belief that he has a meeting with Mary next Wednesday at noon.…”
Section: The Case For Robust Epistemic Generativism About Memorymentioning
confidence: 58%
“…It is a case of justified true belief from unjustified true belief as opposed to knowledge from falsehood. That said, the seat counter case does bear some resemblance to a case discussed by Murphy (). In Murphy's case, someone called Fred has a memory based belief that he has a meeting with Mary next Wednesday at noon.…”
Section: The Case For Robust Epistemic Generativism About Memorymentioning
confidence: 58%
“…10 Essas teses impossibilitam também a obtenção de conhecimento inferencial a partir de crença gettierizada e de crença injustificada, por exemplo. Para mais informações, veja Luzzi (2014Luzzi ( , 2019, Olivier (2019), Murphy (2017). 11 Embora possa haver casos nos quais uma crença verdadeira e uma crença falsa, independentes entre si, sejam os fatores causais e evidenciais de uma outra crença verdadeira que é uma instância de conhecimento, perceba que esse tipo de caso não é um contraexemplo ao princípio CFC.…”
Section: Contrafecho Do Conhecimento (Cfc)unclassified
“…Those who think that knowledge cannot come from falsehood presumably do so on the grounds that beliefs that amount to inferential knowledge cannot be properly based on false beliefs. Peter Murphy (2015) has suggested that a false unjustified belief may still serve as the proper basis for a justified belief. While Murphy's discussion is not directly concerned with knowledge from falsehood, his discussion of proper basing involves a case of a false belief serving as the proper basis for an inferred justified belief.…”
Section: Implications For the Nature And Structure Of Justificationmentioning
confidence: 99%
“…In particular, it belongs to beliefs that are themselves unjustified but nonetheless allow justification to pass through to some beliefs that are validly and competently deduced from them. (Murphy 2015: 11)…”
Section: Implications For the Nature And Structure Of Justificationmentioning
confidence: 99%
See 1 more Smart Citation